Employing ICTS: Teaching & Learning through Literature Digital Reading (LDR) - Aba-Carina Pârlog (Linguaculture)
This article is based on a material produced under the umbrella of and funded by the Erasmus+ research project DILECTINGS (DIgital Literature Educational Competences for Teachers: Intercultural iNclusive Good-practices for Second-language learning), KA220-SCH-2CA4CF2E, coordinated by Prof. dr. Raffaella Leproni, Università degli Studi RomaTre. It was made available for training participants as part of Project Result 2, Module 5 (Creating Digital Stories: Story Writing Toolkit for Teachers) on the project platform. The current version aims to show that the use of technology in a friendly virtual environment is nowadays crucial in order to create a fertile atmosphere for planned teaching/ learning and that Literature Digital Reading (LDR) tools contribute to the development of the modern class substantially and encourage students to become autonomous users of foreign languages. Available ICTs aid educators in making better use of class time due to the impact of technology on the younger generations.